Evaluation of Corrosion Inhibition, Thermo-Oxidative Stability, and Biodegradability of Castor Oil-Based Lubricant - Woma, T. Y.; Ipilakyaa, T. D.; Abdullahi, A. A.; Abdulrahman, A. S.; Olutoye, M. A.; Lawal, S. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Global lubricant demand is on the increase and the continual consumption of mineral oil-based lubricant has devastating environmental impact. Despite the identification of animal fat and vegetable oil as alternatives to mineral oil-based lubricants, there is concern about its sustainability due to the food-versus-lubricant debate. Thus, non-edible vegetable oil-based lubricant development has become a topical area of research. In this paper, the study of physicochemical, rheological, temperature, thermo-oxidative stability, corrosion inhibition and biodegradability properties of castor oil extracted from Nigerian grown castor bean seeds was conducted using standard test methods. The results show that castor oil has specific gravity of 0.955, free fatty acid value of 19.74 mg KOH/g, pH of 5.76, saponification value of 185.41 mg KOH/g and Iodine value of 92.1 gI2/100g oil. An assessment of the rheological and temperature properties of the castor oil gave kinematic viscosity at 400C and 1000C as 280.6 cSt and 77.5 cSt respectively, viscosity index of 33.4, pour point of -23.20C, cloud point of -12.40C and flash point of 2820C. The peroxide value of the castor oil was 8.92 meq/Kg and it was of corrosion grade 0. The castor oil has higher viscosity at 400C, lower viscosity index, and poor physicochemical properties compared to the SAE 20W50. The properties of the castor oil require improvement except its cold flow, flash point and corrosion inhibition properties. The castor oil is highly biodegradable while the SAE 20W50 has poor biodegradability. Therefore, castor oil conforms to ISO VG220 grade lubricant and qualifies to be called a biolubricant.